E-MODULE BASED ON RESEARCH-BASED LEARNING (RBL) ON GLOBAL WARMING MATERIAL: E-MODUL BERBASIS RESEARCH BASED LEARNING (RBL) PADA MATERI PEMANASAN GLOBAL - Nurul Fatimah; Hadi Nasbey; Upik Rahma Fitri (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
The use of learning media is crucial as it can influence the learning process of students, one of which isthe use of modules. Electronic modules (e-modules) are employed due to their interactive nature,appealing design, and ability to facilitate students' learning process. This study aims to (1) develop anelectronic module (e-module) based on Research-Based Learning (RBL) on the topic of globalwarming, and (2) determine the feasibility of the electronic module (e-module) based on Research-Based Learning (RBL) on the topic of global warming. The research method used in this study isdevelopment research utilizing the ADDIE development model. The ADDIE model consists of severalstages: Analyze, Design, Develop, Implement, and Evaluate. However, this study will be conductedonly up to the Develop stage, or product development. The e-module developed adopts a research-basedlearning model focusing on the topic of global warming, supplemented with images, videos, andanimations that are engaging and accessible from various devices.